Analisis Kesalahan Siswa dalam Menyelesaikan Soal Cerita Pecahan Berdasarkan Jenis Kelamin Ditinjau dari Teori Newman - Endri Puji Lestari; Shofan Fiangga (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
This study research to determine the differences in the types of errors and the cause students' errors in solving fraction story problems by male and female students in terms of Newman's theory. This research is using a qualitative approach to the type of case study. The subjects of this study were 3 male and 3 female students in grade VII MTsN 2 Trenggalek. The selection of research subjects was carried out based on the same mathematical ability and the suitability of gender criteria. The data collection techniques are written tests, unstructured interviews, and documentation. Data analysis techniques are data reduction, data presentation, and conclusion drawing. Based on the results of the study, (1) it was not found that male students and female students made reading errors, (2) male students and female students made comprehension errors with the same percentage, the cause was not writing down what was known and asked, (3) only male students made a transformation errors, the cause was choosing the wrong operation, formula, not converting the problem into mathematical form, (4) male students making process skill errors with a higher percentage than female, the cause was student perform the wrong operations, processes, and calculation results, while female students make mistakes in the process and calculation results, (5) male students make encoding error with higher percentage, the cause was students incorrectly or not writing the final answer.